Firewalking: Explanation and the Mind-Body Relationship - Sansom, Jane (The Australian journal of anthropology, 1998)
With specific reference to the Anastenaria, a firewalking ritual performed in the North of Greece, this paper discusses the problem which phenomena such as firewalking poses for anthropological discussion. The relationship between the mind and the body and their existence in the social world is addressed, as I search for a way in which anthropological discourse can approach an explanation of an individual's ability to walk on burning coals unharmed. A brief look at the various explanations provided by different disciplines follows a more detailed review of scientific inquiry into this phenomenon. A critical discussion of the notions of trance, possession and altered states of consciousness introduces the subjective/objective dichotomy. The question is asked: How does the body exist in the world and to what extent does there remain a distinction between body, mind and object?